Ireland : Financial Sector Assessment Program: Technical Note-Macroprudential Policy Framework. (IMF Staff Country Reports; Country Report, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Ireland in the area of the macroprudential policy framework. The current institutional arrangement in Ireland is appropriate for effective macroprudential policy and in line with IMF guidance. The Central Bank of Ireland's analysis of systemic vulnerabilities is sophisticated and timely. The central bank has been introducing a range of macroprudential instruments to contain a buildup of systemic risk in the financial system. Ireland's boom-bust experience amply demonstrates the need for forward-looking action to head off incipient financial problems.